Influencia de la bailoterapia con ritmos nacionales en la salud física y emocional del adulto mayor asociación la Salud Otavalo - Insuasti, María L. (2018)
The present research work consists of describing the influence of bailotherapy with national rhythms for the improvement of the physical and emotional health of the elderly, the elderly group of the Association the Salud of the city of Otavalo belonging to the retired association of the same city. The investigation starts from the theoretical methodological foundation planted by different authors.